Recovering non-pecuniary losses in breach of employment contract under Malaysian law - Ali Mohamed, Ashgar Ali; Shair Mohamad, Mohd Akram; Sardar Baig, Farheen Baig (2017)
Dismissal from employment is the prerogative of the employer. An impending dismissal must be carried out fairly with the affected employee given the right to be heard. When a dismissal has been effected in high-handed manner, it may have real prospect of humiliation and embarrassment to the employee. Besides besmirching his reputation, it can also affect the employee’s ability to seek new employment, forcing him to accept employment offering lower wages than what would have been expected in the type of work, or even causing him ill health, among others. The availability of compensation for non-pecuniary losses such as wounded feelings or the effect of the dismissal on his reputation or the chances of finding other employment arising from the manner of the dismissal were excluded by the House of Lords in their landmark case of Addis v Gramophone Co Ltd [1909] AC 488. Such compensation was disallowed mainly because the common law perceived employment contract as an ordinary commercial contract and that such contract is not intended to shelter the parties from anxiety. The situation in the 21st century is however markedly different from 1909 where with the advancement of information technology, the transmission of information regarding the manner of a dismissal is borderless and thus, having far reaching consequences on the claimant. In light of the above, this paper discusses the high-handed manner of a dismissal, its impact on the employee and the availability of compensation for non-pecuniary losses under the statutory unfair or unjustifiable dismissal. Reference is made to the law and practice in selected countries namely, the United Kingdom, Canada, Australia and New Zealand. In the context of Malaysia, it will be contended that an employee that had been subjected to deplorable acts of victimisation while in employment and any high-handed manner of a dismissal, among others, should be awarded the non-pecuniary compensation.